GABAergic and non-GABAergic projections to the superior colliculus from the auditory brainstem - Mellott, Jeffrey G. (Brain Struct Funct, 2018)
The superior colliculus (SC) contains an auditory space map that is shaped by projections from several subcortical auditory nuclei. Both GABAergic (inhibitory) and excitatory cells contribute to these inputs, but there are contradictory reports regarding the sources of these inputs. We used retrograde tracing techniques in guinea pigs to identify cells in the auditory brainstem that project to the SC. We combined retrograde tracing with immunohistochemistry for glutamic acid decarboxylase (GAD) to identify putative GABAergic cells that participate in this pathway. Following a tracer injection in the SC, the nucleus of the brachium of the inferior colliculus (NBIC) contained the most labeled cells, followed by the inferior colliculus (IC). Smaller populations were observed in the sagulum, paralemniscal area, periolivary nuclei and ventrolateral tegmental nucleus. Overall, only 10% of the retrogradely labeled cells were GAD-immunopositive. The presumptive inhibitory cells were observed in the NBIC, IC, superior paraolivary nucleus, sagulum and paralemniscal area. We conclude that the guinea pig SC receives input from a diverse set of auditory brainstem nuclei, some of which provide GABAergic input. These diverse origins of input to the SC likely represent a variety of functions. Inputs from the NBIC and IC likely provide spatial information for guiding orienting behaviors. Inputs from subcollicular nuclei are less likely to provide spatial information; rather, they may provide a shorter route for auditory information to reach the SC, and could generate avoidance or escape responses to an external threat.